Talent detection and competitive progress in biathlon - a national example - Carlson, R. (Polish Journal of Sport and Tourism, 2011)
The main purpose of this study was to explain later years` success among Swedish biathletes. Sportive talent is regarded an interactional process within the frame of Bronfenbrenner`s ecological model for human development. The national team (the elite group) consisting of 13 individuals was investigated along with a control group - matched in pairs in variables age, sex and athletic performance. All athletes were graduates from the upper secondary education sport schools (RIG sport academies). Data was collected via interviews and observations during training and world cup competitions. Based on quadruples of a year elite biathletes were more often born early in a year compared to controls. Hence, the prevailing system for division in competition classes based on age during adolescence could favour early developers. The elite group athletes revealed more positive experiences from sport academy years - in particular concerning the acting and behaviour of coaches in terms of individualisation in training and reciprocity in communication. Furthermore, controls were more often injured and experienced greater difficulties to carry out sufficient training. The results indicate the negative impact of competition classes based on age per se during adolescence and competence issues referring to sport academy coaches.